Macroeconomics of vertically globalized production - Wong, Chin Yoong (2012)
This thesis investigates the macroeconomic implications of vertically fragmented production by shedding light on three long-standing issues in international macroeconomics: trade-comovement puzzle, China’s syndrome,an dinternational monetary policy coordination. Chapter 3 revisits the tradecomovement puzzle. Existing models of international business cycle, ranging from two-country real business cycle model to simple vertical-specialization model, are known for the inability to reproduce the empirical regularities that economies linked with bilateral trade in intermediate inputs tend to comove more closely. Such modeling-empirics mismatch casts doubt on the role of international trade as transmission mechanism. This thesis contributes to the literature by laying out a medium-scale two-country New Keynesian model with three processing stages fragmented across borders. Doing so allows us to capture the essence of vertical specialization in the form of vertical and processing trade. The model is then estimated using Bayesian method on trade-weighted East and Southeast Asian time series. The estimated model has convincingly demonstrated its ability to replicate neatly the business cycle comovement over a large set of macroeconomic variables. As such, the thesis delivers a message that proper modeling of production fragmentation is a rewarding exercise for solving trade-comovement puzzle. Turning our attention to contemporary issues, the anxiety with respect to the influence of rising China on Asian neighbors has been mounting. Whether China’s rise is benign or malign to Asian neighboring economies remains empirically indecisive. By taking the model into the data of China and East/Southeast Asia, Chapter 4 shows that vertical trade in intermediate inputs between China and East Asia has substantially arisen alongside processing trade in the aftermath of China’s WTO accession. East Asia, as the story goes, specializes at midstream production to produce intermediate goods traded vertically with China which specializes at downstream production for processing export. Nonetheless, vertical trade between China and the developing Southeast Asia is trivial over the same time span. Both regions vertically specialize at downstream production, competing in processing trade against each other. Unsurprisingly then, the impulse response analysis indicates that China’s integration into regional production network has been benign to the advanced East Asian economies through vertical trade, but malign to the developing Southeast Asian economies that have to compete in processing trade.The thesis thus puts forward an argument that macroeconomic interdependence is hugely influenced by the nature of production and trade linkage. For open economies that are vertically and sequentially linked through production fragmentation and network-driven trade, an important question is if there is welfare gain from international monetary policy coordination. Drawn on the model estimated on China, East and Southeast Asia, Chapter 5 revisits this classic issue by proposing two novel views of optimal monetary policy coordination. Firstly, economies with strong trade link are not necessarily the natural candidates for policy coordination. The pattern of trade linkage does matter. Welfare gains from policy coordination can be sizeable only when the member economies vertically specialize at different chains of production and thus complement each other through vertical and processing trade. Another equally if not more important contribution of this thesis is to develop a view of optimal monetary policy coordination as competing objectives of optimal input allocation due to production fragmentation and optimal consumption allocation with home bias. The former has disinflationary bias while the latter has expansionary bias. Were intratemporal elasticity of substitution between home and foreign final goods not equivalent to that between home and foreign intermediate goods, two biases are not counterbalanced. Either way will lead to currency misalignment, ending in inefficient price dispersion of identical goods across borders. Such effect occurs regardless of the genre of trade links. This has reinstated a strong case for international monetary policy coordination.